Planktic foraminiferal proxy development and application to paleoceanographic change in the Southwest Pacific Ocean - Marr, Julene (11669563) (2013)
This thesis investigates the use of foraminiferal calcite geochemical and physical properties as paleoceanographic proxies, to improve identification of past climatic change and provide a more quantitative basis for forecasts of future climate. I have developed and used these proxies on a high resolution, well-dated marine sediment core, MD97 2121 from north of the Subtropical Front (STF) off the eastern central North Island of New Zealand to determine paleoceanographic changes in the South Pacific Gyre since the last glacial period, 25 ka to present. Various analytical methods to measure foraminiferal calcite trace element geochemistry were first investigated using core top samples. Two main analytical techniques were deployed; “pseudo” solution- or laser ablation-based ICPMS analysis. Ratios tested include Mg/Ca, Sr/Ca, Ba/Ca, Zn/Ca, Mn/Ca and Al/Ca. Trace element/calcium ratios Mg/Ca and Sr/Ca values were consistent between these methods, provided that currently recommended ‘Mg-cleaning’ protocols were followed for solution-based measurements. However, discrepancies of up to an order-of-magnitude for Zn/Ca, Mn/Ca and Ba/Ca occurred between solution and laser ablation-based measurements if both oxidative and reductive cleaning techniques were not employed prior to solution-based analysis. Using down-core trace element values Mg/Ca, Zn/Ca, Mn/Ca and Ba/Ca from MD97 2121, coupled with modern core top and plankton-tow samples, multiple geochemical proxies for the SW Pacific Ocean were developed and/or tested. Results suggest that Zn/Ca may act as (i) a surface water mass tracer, in this case differentiating between subtropical and subantarctic surface waters and (ii) a proxy for nutrients. Mg/Ca and Zn/Ca values from different test chambers in Globigerina bulloides were also found to reliably re-construct surface ocean temperature and nutrient stratification. Using these new proxies, coupled with oxygen isotopes, standard Mg/Ca paleothermometry and foraminiferal assemblage data, I show that surface water nutrient and thermal stratification significantly reduced during the last glacial period. In addition, the relative strength of the South Pacific Gyre, which affects the inflow of subtropical water to New Zealand, was a major influence during the last glacial termination. In particular, the period from 17-14.5 ka, otherwise known as the ‘Mystery Interval’, appears to be genuinely anomalous with foraminifera indicating cooling trends while alkenones continue to warm. This may reflect changes to both gyre strength and Antarctic forcing prior to the Antarctic Cold Reversal (14.2-12.5ka) and an offset in the timing of species productivity. The high resolution Mg/Ca paleotemperature record developed here, together with published alkenone paleotemperatures were compared to core MD97 2120, south of the STF to evaluate the relationship between Mg/Ca and alkenones temperatures and how these reflect environmental change. It appears that the season of maximum alkenone and G. bulloides flux varied over the last 25kyr in response to insolation and water mass changes. During the glacial period north and south of the STF alkenone seasonal flux was summer dominated. However, during the Holocene while seasonal alkenone flux remained summer or annual dominated in the north, it shifted to a spring productivity cycle south of the STF. The foraminifera G. bulloides glacial period flux was likely have been spring dominated both north and south of the STF, maintaining a spring bloom cycle south of the STF, while shifting to a summer or annual cycle to the north during the Holocene. These seasonal offsets may have acted to dampen or exacerbate the glacial-Holocene temperature offsets by up to 4°C especially for the surface dwelling, alkenone producing coccolithophores. Seasonality changes of the coccolithophore and foraminifera make direct comparison of alkenone and Mg/Ca G. bulloides paleothermometers challenging. However, despite the complexity, offsets in the paleotemperatures may help to elucidate changes in the paleoceanography. The use of G. bulloides size normalised weight (SNW) as a proxy for surface water carbonate ion concentration ([CO₃⁼]) was investigated by comparing modern SNW data sets from five different ocean regions to their specific environmental variables including [CO₃⁼], chlorophyll-a, nutrient and temperature values. It was identified that the ‘ocean’ from which the foraminifera originated appeared to have the strongest control over shell SNW, potentially reflecting geographically distinct, genetic variations within the G. bulloides species. Within ‘ocean’ regions no consistent environmental variable(s) could be identified that appeared to control shell SNW in all regions. From the 25 ka to present, shell SNWs from the SW Pacific Ocean were compared to the North Atlantic and were found to be heavier during the glacial period regardless of ocean region. This may reflect multiple factors including increased surface ocean CO₃⁼, possibly combined with changes in primary productivity. Calcification of G. bulloides tests appears to be region specific; therefore, proxy calibrations based on shell SNW for one ocean are not applicable to other settings.